(untitled) (Bangladesh Journal of Agricultural Research, 2008)
In field experiments, it is necessary to determine the optimum sample size as well as optimum number of replications if researchers have to use sampling techniques for collecting data from such experiments. Estimates of such optimum sample size and number of replications has been determined for split-split plot design minimizing the variance for a given cost of the experiment per treatment. DOI: http://dx.doi.org/10.3329/bjar.v32i3.542 Bangladesh J. Agril. Res. 32(3) : 403-411, September 2007